Linear widths of the classes $B^{Ω}_{p, θ}$ of periodic functions of many variables in the space $L_q$ - Fedunyk, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain exact order estimates for the linear widths of the classes $B^{Ω}_{p, θ}$ of periodic functions of many variables in the space $L_q$ for certain values of the parameters $p$ and $q$.